The Effectiveness of Using Word Domination Game in Students Vocabulary of Fifth Grade at Miftahul Huda Islamic Elementary School Plosokandang - Rokhim, Muhammad Ghofur (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Vocabulary mastery is the activity to enrich the vocabulary, they master the vocabulary in order to be able to master four language skills. This research discuses about the effectiveness of Word Domination game in students’ vocabulary mastery. The objective of this research is to know “Word Domination game” method in students vocabulary mastery. This research uses quantitative research. The researcher uses pre experimental design for research design. The data collecting method are pretest, treatment, and posttest. The subject of the research is students fifth grade of Miftahul Huda Islamic Elementary School. The mean of posttest is higher than pretest which is 7.27 > 4.33, and the significant is 0.000 < 0.05. In conclusion that “Word Domination game” is significantly effective for students vocabulary mastery of fifth grade at Miftahul Huda Islamic Elementary School. So, Word Domination game was effective method to improve students vocabulary mastery and this method can be applied in the classroom.